Highly diastereoselective formation of stable fulleroids - Schick, Georg; Hirsch, Andreas (Tetrahedron, 1998)
The highly regio- and diastereoselective formation of the cluster opened fulleroid isomers 12 via thermal decomposition of the corresponding pyrazolines 11 is reported. In the diastereomers 12 the protons of the monoalkylated methylene bridge are located above a six-membered ring and the bulkier alkyl groups above a five-membered ring. The corresponding methanofullerenes were not detected and the diastereomeric fulleroids 13 with the methylene bridge proton above a five-membered ring are formed only in traces. The pyrazoline 11a is the first example of a substituted pyrazolino[60]fullerene. The present experimental and computational investigations provide important information on the mechanism of this most fundamental cluster opening process in fullerene chemistry.